Eno-Olivotourism in Douro (Portugal) - Josefina Olivia Salvado; Bebiana Monteiro (Cadernos de Geografia)
Wine and olive oil are fundamental elements of the Douro region’s food and cultural heritage, reflecting ancestral production and consumption practices. The integration of olive oil into wine tourism experiences - Eno-Olivotourism - represents an innovative strategy that contributes to heritage valorisation, enhances tourism competitiveness, and strengthens communication narratives, fostering the development of distinctive content for digital marketing and social media.